Literasi Keuangan, Self-Control, dan Perilaku Konsumtif Dalam penggunaan Buy Now Pay Later pada Generasi Z: Bukti Empiris dari Kota Cirebon - Della Kurnia Sari; Nurhana Dhea Parlina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The aim of this research is to explore how financial literacy and self-discipline impact spending habits concerning “buy now, pay later” (BNPL) services among Generation Z in Cirebon City. This research utilizes a quantitative method with an explanatory framework. Data was gathered through a survey involving 199 individuals who were chosen via purposive sampling, and the analysis was carried out using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that financial literacy positively and significantly influences consumer behavior related to BNPL usage. Similarly, self-discipline also shows a positive and significant impact on consumer habits. These results imply that, in the realm of digital credit, financial awareness and self-control perceptions do not always serve as protective mechanisms; instead, they can sometimes justify persistent spending under certain circumstances. Additionally, these two factors together explain 59. 2% of the variation in consumer behavior. This research highlights the necessity of understanding consumption behavior within the BNPL framework not just through the lens of technological ease but also considering the cognitive and psychological aspects of the users.